Một phương pháp giữ các điểm khớp trong vecto hóa bán tự động không qua làm mảnh - Toàn, Đỗ Năng (Journal of Computer Science and Cybernetics, 2016)
In this paper, we describe a method for keeping junction point in semi automatic vectorizing process. This approach allows to flow the vectorizing without thinning method. The paper also shows the first of maps that can be vectorized and have been tested by MAPSCAN software package that developed in the Pattern Recognition and Image Processing Group. The kind of maps could be as follow: -Scanned maps with boundaries of territorial areas, rivers, routes, specific lines,… - Mechanical drawing maps…